EPJ photovoltaics (EDP Sciences, 2010)
"EPJ Photovoltaics (formerly PV Direct) is an Open Access journal which publishes original, peer-reviewed papers focused in the field of photovoltaic solar energy conversion. Authors in the field of crystalline, polycrystalline, thin film (silicon, CIGS, organic) and third generation PV are called to submit their research letters and regular articles for a fast publication and broad audience (open access)."